2020
DOI: 10.3390/su12218875
|View full text |Cite
|
Sign up to set email alerts
|

Understanding N2O Emissions in African Ecosystems: Assessments from a Semi-Arid Savanna Grassland in Senegal and Sub-Tropical Agricultural Fields in Kenya

Abstract: This study is based on the analysis of field-measured nitrous oxide (N2O) emissions from a Sahelian semi-arid grassland site in Senegal (Dahra), tropical humid agricultural plots in Kenya (Mbita region) and simulations using a 1D model designed for semi arid ecosystems in Dahra. This study aims at improving present knowledge and inventories of N2O emissions from the African continent. N2O emissions were larger at the agricultural sites in the Mbita region (range: 0.0 ± 0.0 to 42.1 ± 10.7 ngN m−2 s−1) than at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…STEP-GENDEC-N2O is a process-based model developed for the Sahelian herbaceous savanna, coupling water budget, aboveground and belowground herbaceous vegetation growth and decay, litter fall (Mougin et al, 1995), soil biogeochemistry (Moorhead and Reynolds, 1991), and soil gaseous emissions (Agbohessou et al, 2023;Bigaignon et al, 2020;Delon et al, 2019). The model simulates the main processes describing the water, C, and N cycling between the atmosphere, vegetation, and soil at daily time steps and finally CO2 and N2O emissions.…”
Section: Model Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…STEP-GENDEC-N2O is a process-based model developed for the Sahelian herbaceous savanna, coupling water budget, aboveground and belowground herbaceous vegetation growth and decay, litter fall (Mougin et al, 1995), soil biogeochemistry (Moorhead and Reynolds, 1991), and soil gaseous emissions (Agbohessou et al, 2023;Bigaignon et al, 2020;Delon et al, 2019). The model simulates the main processes describing the water, C, and N cycling between the atmosphere, vegetation, and soil at daily time steps and finally CO2 and N2O emissions.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Accordingly, to better understand the magnitude of GHG emissions in these systems and develop effective and spatially targeted climate solutions it is important to identify CO2 and N2O emission hotspots and accurately estimate emissions from Sahelian SPSs. The different bottom-up approaches used to estimate large-scale soil CO2 and N2O emissions include the use of "emission factors" (EFs) as proposed by the Intergovernmental Panel on Climate Change (IPCC) (Hergoualc'h et al, 2019;IPCC, 2006), statistical extrapolation of field measurements, and process-based models (Bigaignon et al, 2020;Delon et al, 2019;Li, 2000;Parton et al, 2001). Besides, the top-down approaches integrate atmospheric measurements and atmospheric inversion models (Saikawa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Jain et al (2014) the seasonal integrated fluxes of N 2 O-N were 0.69 and 0.90 kg ha −1 from conventional transplanted rice and SRI planting methods, respectively. Boateng et al (2020) conducted a study in Ghana and reported the seasonal N 2 O emissions ranged from 1.61 to 58.08 kg N 2 O ha −1 , and Gitonga (2020) conducted a study in Kenya and found the seasonal N 2 O emissions ranged from 0.18 to 1.29 kgN 2 O ha −1 . Hadi et al (2010) in Indonesia reported the average N 2 O emissions of 1.97 from intermittently drained plots and −19.7 kgN 2 O ha −1 from continuously flooded plots respectively.…”
Section: E Ect Of Crop Management Practices and Nitrogen Rates On Sea...mentioning
confidence: 99%
“…Nitrous oxide emissions for 2014 and 2017 were taken from Bigaignon et al (2020) who simulated N 2 O fluxes from 2012 to 2017 at the Dahra site using the Sahelian Transpiration Evaporation Productivity model (STEP, Mougin et al 1995;Jarlan et al 2005;Delon et al 2015), coupled to GENeral DEComposition model (GENDEC, Moorhead and Reynolds 1991) and an N 2 O emission model (Li et al 2000). These simulations were compared to measurements made in Dahra in July and November 2013, at the beginning and at the end of the wet season (Delon et al 2017), and in September 2017 in the core of the wet season (Bigaignon et al 2020).…”
Section: Outputsmentioning
confidence: 99%